Evaluation of Medication Use in Malaysian Predialysis Patients - Muhammad Salman, Muhammad Salman; Khan, Amer Hayat; Adnan, Azreen Syazril; Syed Sulaiman, Syed Azhar; Shehzadi, Naureen; Asif, Nauman; Hussain, Khalid; Saleem, Fahad; Raza, Muhammed Hussnain; Farooq, Muhammad Shahid (Medknow Publications, 2017)
Chronic kidney disease (CKD) patients suffer from multiple comorbidities and complications as a cause or consequence of kidney disease. Information regarding medicationprescribing patterns in predialysis patients is sparse. We conducted a retrospective study to evaluate the medication prescription patterns among predialysis patients. Medical records (both paper based and computerized) of patients at CKD Resource Centre, Hospital Universiti Sains Malaysia, were reviewed. A total of 615 eligible cases were included in the study. The mean number of medications prescribed per patient was 8.22 ± 2.81, and medication use was correlated to the renal function (stage 3a < stage 3b < stage 4 < stage 5; P <0.001). The top three prescribed medication groups were found to be lipid-lowering agents, calcium channel blockers, and antiplatelet agents. Some medication classes such as nonaluminum/noncalcium phosphate binders, erythropoietin-stimulating agents, and renin-angiotensin-aldosterone system blockers, particularly in advanced stage, were found to be underutilized. In conclusion, predialysis patients are prescribed a large number of medications. Our findings highlight the need for assessing the impact of current medication-prescribing patterns on morbidity and mortality rates in Malaysian predialysis population.